A superrobust superhydrophobic PSU composite coating with self-cleaning properties, wear resistance and corrosion resistance. Issue 13 (26th January 2016) - Wang, Huaiyuan; Zhang, Xiguang; Liu, Zhanjian; Zhu, Yixing; Wu, Shiqi; Zhu, Yanji
Abstract : In this study, a superhydrophobic polysulfone (PSU) composite coating with a high water contact angle (WCA) of 159° and a low slide angle (SA) of only 3.5° has been fabricated through a simple thermal spraying method. Abstract : In this study, a superhydrophobic polysulfone (PSU) composite coating with a high water contact angle (WCA) of 159° and a low slide angle (SA) of only 3.5° has been fabricated through a simple thermal spraying method. The ductility and mechanical properties of the PSU composite coating were improved effectively through the combination of the cross-linking ability of PVDF and the special multilayer structure of MMT. The wear resistance of the prepared coating is approximately 14.3 times longer than that of commercial fluorocarbon coating. Simultaneously, the prepared superhydrophobic coating also possesses outstanding corrosion resistance; the corrosion current and corrosion potential decreased from 10 −0.9 to 10 −3.6 μA cm −2 and from −803 to −218 mV, respectively. Furthermore, the prepared coating demonstrated superb self-cleaning, anti-fouling and durability properties. It is believed that this robust superhydrophobic PSU/PVDF/MMT–PDMS composite coating may provide the possibility to realize large-scale fabrication and applications in industry.